مكافحة الفساد الإداري والمالي في العراق والأردن للمدة "2003-2018" - كزار، مصطفى حميد; كاظم، حسام علي (الجامعة العراقية - مركز البحوث والدراسات الإسلامية, 2023)
إن استشراء ظاهرة الفساد المالي والإداري في العراق جاءت نتيجة توافر المناخ والبيئة الملائمة، مما أدى لانتشاره بشكل سريع في جميع مؤسسات الدولة العراقية، خاصة بعد الاحتلال الأمريكي عام 2003، لذا هدف البحث إلى دراسة ظاهرة الفساد في العراق ودور المؤسسات المحلية في مكافحة هذه الظاهرة في الدوائر الحكومية، ضمن فرضية مفادها إن ضعف المؤسسات والهيئات المسؤولة عن مكافحة الفساد في أدى إلى استشراء ظاهرة الفساد بين الموظفين في الوحدات الإدارية الحكومية في العراق. فعلى الرغم من محاولات القضاء على ظاهرة الفساد في العراق من خلال اتخاذ جملة من الإجراءات الرقابية والتشريعية والتنفيذية إلى جنب التشكيلات الحكومية كديوان الرقابة المالية، ومكاتب المفتش العام، ثم تشكيل المجلس المشترك لمكافحة الفساد عام 2007 التابع لهيئة النزاهة العراقية، ليكون الإطار التنسيقي الجامع لكافة الأجهزة الرقابية على الصعيد المحلي والدولي لمكافحة الفساد في العراق، فإن هذه الظاهرة لازالت تسجل درجات مرتفعة حسب مؤشر المنظمات المحلية والدولية. The widespread phenomenon of financial and administrative corruption in Iraq was the result of the availability of climate and the appropriate environment, which led to its rapid spread in all institutions of the Iraqi state, especially after the US occupation in 2003, so the aim of the research to study the phenomenon of corruption in Iraq and the role of local institutions in fighting this phenomenon in Government departments, within the hypothesis that the weakness of institutions and bodies responsible for fighting corruption led to the spread of corruption among employees in government administrative units in Iraq. Despite the attempts to eliminate the phenomenon of corruption in Iraq by taking a number of regulatory, legislative and executive measures, along with government formations such as the Office of Financial Supervision, and the offices of the Inspector General, and then the formation of the Joint Council for Fighting Corruption in 2007 of the Iraqi Integrity Commission, to be the coordinating framework Combining all supervisory departments at the local and international level to fight corruption in Iraq, this phenomenon is still scoring high according to the index of local and international organizations.
Keywords: ظاهرة الفساد -- الفساد المالي -- الرقابة الإدارية -- العراق -- الأردن